Management of bioprosthetic cardiac valve thrombosis. Issue 4 (2nd October 2018) - Fan, Jerry; Lipatov, Kirill; Lane, Wes; Mixon, Timothy
Abstract: Valvular thrombosis is a known complication of bioprosthetic valve replacement that usually occurs within a year of implantation. Four-dimensional computed tomography is quickly becoming the gold standard to directly visualize thrombus. Current guidelines for prophylaxis include aspirin for all bioprosthetic valve replacements, dual antiplatelet therapy for aortic valves, and anticoagulation for mitral valves. However, new trials have suggested single-agent antiplatelet therapy or anticoagulation for treatment of bioprosthetic valve thrombosis. Three cases are presented that illustrate the use of anticoagulants and new techniques for detecting thrombosis on imaging.